Human Capital dan Tata Kelola Terhadap Tingkat Keberhasilan BUMDes Dengan Kinerja Keuangan Sebagai Variabel Mediasi - Suryani Yuli Astuti; Ira Megasyara (Politeknik Ganesha Medan, 2023)
The government's efforts to realize people's welfare are carried out evenly in various fields, one of which is the welfare of the economic community both in urban and rural areas. As a follow-up to efforts to increase the economic welfare of rural communities, the government initiated the Establishment of Village Owned Enterprises or commonly known as BUMDesa. As the basis for the establishment of BUMDes, namely in the framework of launching village community initiatives, developing village potential, managing and utilizing the village's natural resource potential, human resources that have the potential to manage, and with capital participation from the village government in the form of village wealth financing handed over to be borne as part of BUMDes business. This study aims to determine the effect of human capital, governance on the success rate of BUMDes with financial performance as a mediating variable. This study used quantitative research methods, while data collection techniques were carried out using documentation and questionnaires. The sample used in this study was selected using the purposive sampling method. The data obtained was then analyzed using the SmartPLS program. The results showed that human capital had a significant negative effect on financial performance and village success, governance had a significant negative effect on village success but a significant positive effect on financial performance, financial performance had a significant positive effect on BUMDes success, financial performance had no direct effect on capital human resources and the success of village governance.